2017
DOI: 10.1016/j.celrep.2017.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Set2 Methyltransferase Facilitates DNA Replication and Promotes Genotoxic Stress Responses through MBF-Dependent Transcription

Abstract: SummaryChromatin modification through histone H3 lysine 36 methylation by the SETD2 tumor suppressor plays a key role in maintaining genome stability. Here, we describe a role for Set2-dependent H3K36 methylation in facilitating DNA replication and the transcriptional responses to both replication stress and DNA damage through promoting MluI cell-cycle box (MCB) binding factor (MBF)-complex-dependent transcription in fission yeast. Set2 loss leads to reduced MBF-dependent ribonucleotide reductase (RNR) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 65 publications
4
21
0
Order By: Relevance
“…Our findings are in agreement with recent results reporting that loss of the Set2 histone H3 lysine 36 (H3K36) methyl transferase generates reduced MBF-dependent ribonucleotide reductase (cdc22 + ) expression, causing a drop in the dNTP pools, abnormal replication origin firing, S phase delay and genotoxic stress (Pai et al, 2017). As in the rum1Δ ste9Δ mutant, the delay in S phase and the replication stress can be supressed in set2Δ cells by increasing the dNTP levels by deleting the MBF repressor nrm1 + (our work) or yox1 + (Pai et al, 2017) or the RNR inhibitor spd1 + (Liu et al, 2003;Håkansson et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in agreement with recent results reporting that loss of the Set2 histone H3 lysine 36 (H3K36) methyl transferase generates reduced MBF-dependent ribonucleotide reductase (cdc22 + ) expression, causing a drop in the dNTP pools, abnormal replication origin firing, S phase delay and genotoxic stress (Pai et al, 2017). As in the rum1Δ ste9Δ mutant, the delay in S phase and the replication stress can be supressed in set2Δ cells by increasing the dNTP levels by deleting the MBF repressor nrm1 + (our work) or yox1 + (Pai et al, 2017) or the RNR inhibitor spd1 + (Liu et al, 2003;Håkansson et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The correct supply of deoxyribonucleoside triphosphates (dNTPs) during S phase is crucial in maintaining genome integrity (Chabes and Stillman, 2007;Fleck et al, 2013). Recently, it has been shown that reduced MBF-dependent ribonucleotide reductase (RNR) expression generates DNA replication stress and checkpoint activation, phenotypes that can be reversed by increasing the dNTP pools (Pai et al, 2017). Low levels of RNR provide sufficient dNTPs for mitochondrial DNA synthesis and for DNA repair in quiescent cells and during the G1 phase of the cell cycle, but RNR levels and activity have to increase to high levels as cells enter S phase (Stillman, 2013).…”
Section: Fission Yeast Rum1 and Ste9 Are Essential For Extending G1 Imentioning
confidence: 99%
See 1 more Smart Citation
“…Further support for this was also recently provided by Pai et al. , who showed that Set2 in S. pombe is required for efficient DNA replication by regulating the MBF transcriptional program ( 44 ). However, the mechanistic basis by which Set2 controls S-phase progression and proper checkpoint activation remains unknown.…”
Section: Resultsmentioning
confidence: 55%
“…This contradiction may be explained by the recent finding that the high speed of a progressing fork can induce DNA replication stress and slowdown the cell cycle [93]. On the other hand, the dNTP concentrations in yeast are controlled by multiple genes, and some of them are associated with mitotic entry or replication stress response [94,95], raising the complexity of interpretation compared with cultured cells. Moreover, it can be speculated that the embryonic cell cycle of metazoans controlled by dNTP may be underlying by further yet unknown mechanisms.…”
Section: Mechanisms Of Cell Cycle Control By Dntpmentioning
confidence: 99%